Recent advances and future prospective of topical and transdermal delivery systems - Tapfumaneyi, Pronalis; Imran, Mohammad; Mohammed, Yousuf; Roberts, Michael S. (Frontiers in Drug Delivery, 2022)
Recent advances in topical and transdermal drug delivery systems have enabled targeted delivery of therapeutics to the site of action by enhancing drug permeation across the stratum corneum and an increased bioavailability. Although various technological advancements have been made, some dermatoses are still presented with limited treatment options due to potential adverse effects and challenges in formulation development. To address some of the limitations posed by conventional dermatotherapy, nano-based technologies have been developed and have demonstrated significant improvement in dermatotherapy. Their distinct physicochemical properties demonstrate their overall superior therapeutic efficacy in providing sustained and effective targeted drug release, as well as improved solubility of hydrophobic actives with optimized drug formulations. These nanocarriers are commonly classified as polymeric, lipid-based, metallic, and vesicular nanocarriers, including nanoemulsions, nanofibers and microneedles. The aim of this mini-review is to address recent advances in nano-based technologies, with a brief insight on some of the current and prospective technologies and approaches aimed at improving transdermal delivery.